2015
DOI: 10.1371/journal.pone.0145365
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Characterization of Honey Bee (Apis mellifera) Pollen Foraging Based on Non-Overlapping Paired-End Sequencing of Nuclear Ribosomal Loci

Abstract: Identifying plant taxa that honey bees (Apis mellifera) forage upon is of great apicultural interest, but traditional methods are labor intensive and may lack resolution. Here we evaluate a high-throughput genetic barcoding approach to characterize trap-collected pollen from multiple North Dakota apiaries across multiple years. We used the Illumina MiSeq platform to generate sequence scaffolds from non-overlapping 300-bp paired-end sequencing reads of the ribosomal internal transcribed spacers (ITS). Full-leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 64 publications
0
74
0
Order By: Relevance
“…It has been shown by at least one study (Pornon et al., ) that as few as five pollen grains of a target species can generate at least 10‐fold more sequences than a negative control (water only). Rarefaction of field‐collected pollen samples has shown that a relatively complete list of species‐level assignments is recovered with approximately 50,000 reads (Cornman, Otto, Iwanowicz, & Pettis, ), while another study found that only 2,000–3,000 high‐quality reads (4,000–6,000 raw reads) per sample were sufficient to identify 95% of the diversity (Sickel et al., ). The relationship between number of sequencing reads and detection limit of rare species is likely to be strongly dependent on the study system, and particularly the idiosyncrasies and biases of the species in the study system.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by at least one study (Pornon et al., ) that as few as five pollen grains of a target species can generate at least 10‐fold more sequences than a negative control (water only). Rarefaction of field‐collected pollen samples has shown that a relatively complete list of species‐level assignments is recovered with approximately 50,000 reads (Cornman, Otto, Iwanowicz, & Pettis, ), while another study found that only 2,000–3,000 high‐quality reads (4,000–6,000 raw reads) per sample were sufficient to identify 95% of the diversity (Sickel et al., ). The relationship between number of sequencing reads and detection limit of rare species is likely to be strongly dependent on the study system, and particularly the idiosyncrasies and biases of the species in the study system.…”
Section: Discussionmentioning
confidence: 99%
“…ITS sequencing followed methods described more fully in Cornman et al [27], in which an approximately 900-bp fragment is subjected to 300-bp paired-end sequencing, recovering non-overlapping fragments of the ITS1 and ITS2 spacer regions. Briefly, amplicons were produced in two steps, first using ‘standard’ primers to generate a high concentration of input template, followed by less efficient ‘fusion’ primers that incorporate exogenous sequencing adapters.…”
Section: Methodsmentioning
confidence: 99%
“…While fungal coamplification can lead to sequencing failure when using Sanger sequencing, the impact is low, but still significant. In HTS DNA metabarcoding studies, fungal contamination will be sequenced alongside the taxa of interest (i.e., plants) and may comprise a significant proportion of the sequencing reads (e.g., Cornman et al 2015). This will not prevent sequencing and identification of plant species, but it may increase the number of reads required per sample, therefore limiting the number of samples that can be analyzed.…”
Section: Component 2: Genetic Markersmentioning
confidence: 99%